Understanding the Burden of Disease in Nepal: a Call for Local Evidence - Devleesschauwer B, Ale A, Duchateau L, Pun SB, Pandey BD, Speybroeck N Dorny P, Lake R, Dhakal P (Journal of Nepal Health Research Council, 2013)
The burden of disease, most commonly expressed in terms of Disability-Adjusted Life Years, has become a crucial component in decision making processes within the health sector. In Nepal, however, burden of disease estimates are scarce and lack representativeness. To improve our understanding of the burden of disease in Nepal and thereby increase the efficiency of health policies, there is an urgent need to strengthen thelocal evidencebased. All relevant stakeholders should therefore collaborate to generate new data, improve existing data generation mechanisms, make generated data available, and optimize the use of available data.